Increased grain yield with improved photosynthetic characters in modern maize parental lines - Cong-feng LI; Zhi-qiang TAO; Peng LIU; Ji-wang ZHANG; Ke-zhang ZHUANG; Shu-ting DONG; Ming ZHAO (Journal of Integrative Agriculture, 2015)
The grain yield of maize has increased continuously in past decades, largely through hybrid innovation, cultivation technology, and in particular, recent genetic improvements in photosynthesis. Elite inbred lines are crucial for innovating new germplasm. Here, we analyzed variations in grain yield and a series of eco-physiological photosynthetic traits after anthesis in sixteen parental lines of maize (Zea mays L.) released during three different eras (1960s, 1980s, 2000s). We found that grain yield and biomass significantly increased in the 2000s than those in the 1980s and 1960s. Leaf area, chlorophyll, and soluble protein content slowly decreased, and maintained a higher net photosynthesis rate (Pn) and improved stomatal conductance (Gs) after anthesis in the 2000s. In addition, the parental lines in the 2000s obtained higher actual photochemistry efficiency (ΦPSII) and the maximum PSII photochemistry efficiency (Fv/Fm), which largely improved light partitioning and chlorophyll fluorescence characteristic, including higher photochemical and photosystem II (PSII) reaction center activity, lower thermal energy dissipation in antenna proteins. Meanwhile, more lamellae per granum within chloroplasts were observed in the parental lines of the 2000s, with a clear and complete chloroplast membrane, which will greatly help to improve photosynthetic capacity and energy efficiency of ear leaf in maize parental lines. It is concluded that grain yield increase in modern maize parental lines is mainly attributed to the improved chloroplast structure and more light energy catched for the photochemical reaction, thus having a better stay-green characteristic and stronger photosynthetic capacity after anthesis. Our direct physiological evaluation of these inbred lines provides important information for the further development of promising maize cultivars.